2021
DOI: 10.1016/j.psj.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the mTOR signaling pathway and ovarian aging in peak-phase and late-phase laying hens

Abstract: The molecular mechanisms underlying reproductive aging in avian species are poorly understood. Previous studies have shown the importance of mechanistic target of rapamycin ( mTOR ) signaling pathway in aging. In this study, we investigated the relationship between the mTOR signaling pathway and ovarian aging in the peak phase and late phase of egg production in laying hens. The egg production rate and egg quality were tracked for 5 consecutive weeks in 30-week-old and 70-week-old Dawu J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…2 ). Although the observed changes in levels were small (1.5-fold or less) in these situations, the magnitudes of these changes were consistent with those reported in previous studies [ 34 , 35 ]. In contrast, we found that treatment with MHY1485 alone (under non-irradiation conditions) provided limited increase in the levels of p-mTOR and downstream targets in CT26 and LLC ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…2 ). Although the observed changes in levels were small (1.5-fold or less) in these situations, the magnitudes of these changes were consistent with those reported in previous studies [ 34 , 35 ]. In contrast, we found that treatment with MHY1485 alone (under non-irradiation conditions) provided limited increase in the levels of p-mTOR and downstream targets in CT26 and LLC ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In laying hens, productive performance and egg quality are strictly linked to ovarian performance. One of the most dominant factors that cause ovarian damage is oxidative stress which positively correlates with high productivity and the aging process ( Finkel and Holbrook, 2000 ; Hao et al, 2021 ). Dysfunction and aging of the ovaries can lead to detrimental effects for poultry performance, reproductive activity, hatching rate, product quality and life span.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that differentially expressed genes (DEGs) were associated with high rates of egg production in the chicken hypothalamic–pituitary–ovarian axis via the transcriptome and identified DEGs that regulate the mTOR signaling pathway, the Jak-STAT signaling pathway, tryptophan metabolism, and the PI3K-Akt signaling pathways in the HPO axis in laying hens [ 71 ]. In vitro, chicken granulosa cells treated with the mTOR agonist MHY1485 (mTOR activator) showed significantly enhanced granulosa cell proliferation, inhibited apoptosis, and significantly increased mTOR-signaling-related gene (ribosomal protein S6 kinase (S6K) , eIF4E binding protein 1 (4E-BP1) , and protein kinase C (PKC)) expression in the peak phase (30-week-old) and late phase (70-week-old) laying hens [ 72 ]. Recent evidence also suggests that the mTOR signaling pathway plays important roles in folliculogenesis [ 73 ], ovarian cell proliferation, steroidogenesis [ 74 ], and oocyte maturation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%